2019
DOI: 10.1080/01635581.2018.1559935
|View full text |Cite
|
Sign up to set email alerts
|

TAS2R38 Bitterness Receptor Genetic Variation and Risk of Gastrointestinal Neoplasm: A Meta-Analysis

Abstract: Genetic variation in TAS2R38 bitterness taste receptor could alter the efficacy of molecular sensing, hence may be associated with cancer risk. Thus, we performed a meta-analysis to verify the association between the risk of gastrointestinal (GI) neoplasm and TAS2R38 genetic variation. Studies with TAS2R38 diplotype distribution and GI neoplasm phenotypes were searched from PubMed, EMBASE and SCOPUS, and five articles including eight studies were finally selected. The association between diplotype and neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…For the hub gene TAS2R38, encoding bitterness taste receptor, influences the progression of adenomatous polyps by dietary vitamin C and folic acid (50). Other studies show that genetic variation in TAS2R38 is thought to be associated with gastrointestinal risks by modifying dietary intake (51,52). In our research, this gene is associated with the trait of overall survival and the mean methylation levels of TAS2R38 was lower in READ (Supplementary Figure 8C).…”
Section: Discussionsupporting
confidence: 62%
“…For the hub gene TAS2R38, encoding bitterness taste receptor, influences the progression of adenomatous polyps by dietary vitamin C and folic acid (50). Other studies show that genetic variation in TAS2R38 is thought to be associated with gastrointestinal risks by modifying dietary intake (51,52). In our research, this gene is associated with the trait of overall survival and the mean methylation levels of TAS2R38 was lower in READ (Supplementary Figure 8C).…”
Section: Discussionsupporting
confidence: 62%
“…For instance, thyrocyte-expressed T2Rs regulate the production of triiodothyronine and thyroxin and are associated with the risk of papillary thyroid carcinoma [16,17]. The genetic variations in TAS2R38 also modified the risk of gastric and colorectal cancer [13,14,18]. Observational studies reported that those genetic variations were associated with body fatness.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] have examined the role of bitter taste perception in cancer development, focusing on the question of whether genetic variations of TAS2Rs impact the risk for developing cancer directly as well as indirectly via different dietary intake caused by the gene-mediated variability of bitter taste sensitivity. Within the scientific community, the following hypotheses from different perspectives are discussed: (i) an increased bitterness perception leads to the avoidance of bitter-tasting foods with health-promoting phytochemicals and, as a consequence, increases cancer risk [ 36 , 38 ]; (ii) an elevated sensitivity of TAS2Rs to bitter-tasting compounds is protective against bitter-tasting carcinogenic compounds, leading to a decreased cancer risk [ 37 , 40 , 41 ]; (iii) cancer risk is influenced by genetic variants via TAS2R-related, tissue-specific functions [ 44 ].…”
Section: Resultsmentioning
confidence: 99%